PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN DI RUMAH MAKAN KAMPOENG SAWAH KABUPATEN BANDUNG - Widjaja, Yani Restiani; Rahmat, Febi Dwi Jayanti (EKSPANSI, 2017)
Abstract: This research aims to know that influence of quality product and price of purchase decision on Kampoeng Sawah Restaurant. Used the incidental sampling method with 100 persons. Analytical methods used multiple regression analysis. The result based on regression anaylisis: Y = 0,430 + 0,376 . R Square explained that 48,1% of purchase decisions can be explained by quality product and price, and while the rest 50,9% was explained by other variable outside in this research. Hypothesis testing using t test showing that dependent variable quality product (X1) and price (X2) is affect to the independent variable purchase decision (Y) in parsial. Then through the F test can be seen that the quality product (X1) and price (X2) simultaneously affect to the dependent variable is purchase decision (Y). Keywords: Product, Quality Product, Price, Purchase Decision